Analysis of Bending Strength of Inert Gas Tungsten Welded Connections with Variations in Argon Gas Discharge and Strong Current on Aluminum 5083: Analisa Kekuatan Bending Sambungan Las Tungsten Inert Gas dengan Variasi Debit Gas Argon dan Kuat Arus pada Aluminium 5083 - Purgiantono, Purgiantono; Fahruddin, A'rasy (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study was to determine the bending strength of the weld in the connection process with Tungsten Inert Gas (TIG) to the 5083 series aluminum (Al) plate 6 mm thick, the welding was carried out with various current strength treatments, namely 130 A, 140 A, 150 A. and Argon gas discharge of 5 lt/minute, 10 lt/minute, 15 lt/minute in each welding process, and also to find out the defects in the weld area after the bending test was carried out. The method used in this study is the analytical method, which is the method used to test by adding different treatments of current and gas discharge variations during the specimen welding process, so that later on we will get a different welding strength difference in each specimen. From the results obtained from the research on this sample, welding using Argon gas discharge which is